2016
DOI: 10.1007/s10796-016-9691-5
|View full text |Cite
|
Sign up to set email alerts
|

Fostering distributed business logic in Open Collaborative Networks: an integrated approach based on semantic and swarm coordination

Abstract: Given the great opportunities provided by Open Collaborative Networks (OCNs), their success depends on the effective integration of composite business logic at all stages. However, a dilemma between cooperation and competition is often found in environments where the access to business knowledge can provide absolute advantages over the competition. Indeed, although it is apparent that business logic should be automated for an effective integration, chain participants at all segments are often highly protective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 72 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Dynamic capabilities are strengthened by organizational routines and managerial skills, thus marking an enterprise’s adaptability to integrate and reconfigure strategic and business activities to address new frames of lean competition (Doz and Kosonen, 2010). This scenario also creates a dilemma between collaboration and competition, which are both relevant for SMEs because their lack of resources, knowledge, and competencies motivates them to adopt alliance solutions to achieve ambidexterity (Appio, Cimino, Lazzeri, Martini, and Vaglini, 2018; Lubatkin et al, 2006; Zimmermann, Raisch, and Birkinshaw, 2015). Hence, organizational ambidexterity can be considered a measure of organizational agility and adaptability (Birkinshaw and Gibson, 2004; Wei, Yi, and Guo, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Dynamic capabilities are strengthened by organizational routines and managerial skills, thus marking an enterprise’s adaptability to integrate and reconfigure strategic and business activities to address new frames of lean competition (Doz and Kosonen, 2010). This scenario also creates a dilemma between collaboration and competition, which are both relevant for SMEs because their lack of resources, knowledge, and competencies motivates them to adopt alliance solutions to achieve ambidexterity (Appio, Cimino, Lazzeri, Martini, and Vaglini, 2018; Lubatkin et al, 2006; Zimmermann, Raisch, and Birkinshaw, 2015). Hence, organizational ambidexterity can be considered a measure of organizational agility and adaptability (Birkinshaw and Gibson, 2004; Wei, Yi, and Guo, 2014).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Another interesting research avenue may be the one that tries to simulate -factually and counterfactually (Malerba et al, 1999) -industrial dynamics, leveraging upon the wide range of dimensions identified. In a similar vein, a multi-agent system can be built up in which interesting biologically oriented algorithms such as stigmergy can allow managers and policy makers to foresee discontinuities (Appio et al, 2014b).…”
Section: Provocations For Future Researchmentioning
confidence: 99%
“…The service users signed to the privacy policy of providers unknowingly for providing the authorization to them for collecting and sharing the personal identification information of user while accessing the web services [11]. When accepting the policies of providers, some users thought that they secured their privacy ASTESJ ISSN: 2415-6698 information, but their rights are surrendered to the providers [12,13]. This research work aims to reduce the disclosure of privacy related information by using prevalent semantic web based technologies.…”
Section: Introductionmentioning
confidence: 99%